The Almanac of AMG UMP YASA Programme 2021 2022 - Hanisah, Kasbon; Azimah, Ahmad Zaki; Noor Azlinda, Zainal Abidin (2023)
t is said that learning a new language opens a whole new world of opportunities, and the Akademi Menara Gading Universiti Malaysia Pahang Yayasan Al-Sultan Abdullah Programme (AMG UMP YASA) 2021-2022 is a perfect reflection of that ideal.